The Effect of Operating Cash Flow on Cash Dividends and Stock Prices as Intervening Variables in Mining Sub-Sector Companies Listed on the Bursa Efek Indonesia 2018-2022 - Nurul Rizki Lestari; Achmad Fadjar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The benefits of cash flow to estimate future cash flows to determine a company's ability to pay dividends to shareholders, interest payments and loan principal to creditors. The development of these mining projects seems to have an impact on dividend distribution or payment, although profits are increasing, but many companies have become unstable in distributing dividends to their shareholders. This study aims to assess the influence of operating cash flow and cash dividends on stock prices as intevening variables. In this study, the data used is panel data, which is a combination of time series data and cross section data. The time series data used is 2018-2022. The population in this study is all mining sub-sector companies listed on the Bursa Efek Indonesia. The determination of the sample in this study was carried out using the purposive sampling method, with the main criterion of LQ45 index companies. The results of this study found that Operating Cash Flow has an effect on Cash Dividends, then Cash Dividends have an effect on Stock Prices. Keywords: Operating Cash Flow, Cash Dividends, Stock Prices